Factors Influencing The Use Of Injectable Contraceptive Devices In Fertilizing Couples - Yolanda, Silvia; Rohimah, Cucu; Nurjasmi, Emi; Restiana, Leza Fidyah; Pratiwi, Vita; Oktya, Tita (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
The use of contraceptives was observed to decrease along with the increase in economic status. It was recorded that only 43.24% of PUS with the best economic status used contraceptives. The purpose of this study was to determine the Factors Influencing the Use of Injectable Contraceptives in Fertile Age Couples at TPMB Bidan M Rangkapan Jaya Depok. This study used a quantitative design. with a cross-sectional design. The study was conducted at TPMB Bidan M Rangkapan Jaya Depok with a time span from May-September 2023. The sample in this study was WUS who used contraceptives at TPMB Bidan M Rangkapan Jaya Depok from May-July 2023 as many as 86 people. The data analysis used was the Chi square test. The results of the study showed that there was a significant relationship between age and use of contraceptives (p=0.010), education and use of contraceptives (p=0.012), employment and use of contraceptives (p=0.001), number of children and use of contraceptives (p=0.001), and knowledge and use of contraceptives (p=0.017). This study concluded that there was a significant relationship between the variables of age, education, employment, number of children, and knowledge with the use of contraceptives.